2015
DOI: 10.1128/jvi.00104-15
|View full text |Cite
|
Sign up to set email alerts
|

The Glycoprotein Precursor Gene of Junin Virus Determines the Virulence of the Romero Strain and the Attenuation of the Candid #1 Strain in a Representative Animal Model of Argentine Hemorrhagic Fever

Abstract: The New World arenavirus Junin virus (JUNV) is the causative agent of Argentine hemorrhagic fever (AHF), a potentially deadly disease endemic to central regions of Argentina. The live-attenuated Candid #1 (Can) strain of JUNV is currently used to vaccinate the human population at risk. However, the mechanism of attenuation of this strain is still largely unknown. Therefore, the identification and functional characterization of viral genetic determinants dictating JUNV virulence or attenuation would significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
4
57
0
1
Order By: Relevance
“…This is in line with the findings of previous studies performed by others and us, in which GPC was identified to be the major viral factor for the attenuation of the vaccine strain of JUNV (14,16,22). Consistent with our previous report, rMACV infection was lethal to IFN-␣␤/␥ R Ϫ/Ϫ mice (15,18).…”
Section: Figsupporting
confidence: 82%
See 3 more Smart Citations
“…This is in line with the findings of previous studies performed by others and us, in which GPC was identified to be the major viral factor for the attenuation of the vaccine strain of JUNV (14,16,22). Consistent with our previous report, rMACV infection was lethal to IFN-␣␤/␥ R Ϫ/Ϫ mice (15,18).…”
Section: Figsupporting
confidence: 82%
“…It has been established that the Cd#1 GPC renders pathogenic JUNV avirulent in a mouse model and in guinea pigs (14,16). To determine if Cd#1 GPC also renders MACV fully attenuated in vivo, rMACV/ Cd#1-GPC was intraperitoneally inoculated into IFN-␣␤/␥ R Ϫ/Ϫ mice, which succumb to parental rMACV infection (18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy overcomes safety concerns affecting other live attenuated vaccine approaches currently licensed, which are based on a limited number of amino acid substitutions (67). Particularly relevant to arenaviruses, a single amino acid mutation (F427I) within GP2 of the pathogenic XJ13 strain of JUNV attenuated XJ13 neurovirulence in suckling mice (25,26) and was also highly attenuating in the guinea pig model of AHF although it was insufficient to prevent virus dissemination and mild clinical and pathological symptoms (68). These findings suggest that similar limited genetic changes may result in reversion of Candid#1 to a more virulent form, which raises safety concerns and further supports arguments for the development of arenavirus live attenuated vaccines based on alternative approaches involving more drastic changes to the viral genome, such as the rearrangement of the viral genome proposed in the present study.…”
Section: Discussionmentioning
confidence: 99%